The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.37366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Baska Mask Versus Proseal Laryngeal Mask Airway in Elective Surgeries Under General Anaesthesia: A Randomized Clinical Trial

Abstract: BackgroundBaska Mask (BM) is a third-generation supraglottic airway device with a self-inflating cuff. This study aimed to evaluate the efficacy of the BM compared to ProSeal laryngeal mask airway (PLMA) regarding insertion time, ease of insertion, and oropharyngeal seal pressure in patients undergoing elective surgeries under general anesthesia for less than two hours. MethodsThis prospective, randomized, double-blind comparative study was done on 64 patients randomly divided into two groups, with 32 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…BIS was significantly higher in B group compared to E group regarding measurements at baseline, after induction/before laryngoscopy, after laryngoscopy, during intubation/insertion and at 1, 3,5,10,20,30, 40, 50, 60, 90 and 120 min. Peak airway pressure was significantly higher in E group regarding measurements at baseline after induction/before laryngoscopy, after laryngoscopy, during intubation/insertion and at 1, 3,5,10,20,30, 40, 50, 60, 90 and 120 min. Also, leak pressure was significantly higher in E group compared to B group at all times of measurements.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…BIS was significantly higher in B group compared to E group regarding measurements at baseline, after induction/before laryngoscopy, after laryngoscopy, during intubation/insertion and at 1, 3,5,10,20,30, 40, 50, 60, 90 and 120 min. Peak airway pressure was significantly higher in E group regarding measurements at baseline after induction/before laryngoscopy, after laryngoscopy, during intubation/insertion and at 1, 3,5,10,20,30, 40, 50, 60, 90 and 120 min. Also, leak pressure was significantly higher in E group compared to B group at all times of measurements.…”
mentioning
confidence: 80%
“…In terms of the intubation characteristics of the two studied groups, table (5) showed that there was a significant difference between the groups regarding insertion time, but there was no significant difference between studied groups as regards anesthesia time, insufflation time and removal time (Table 5). As regards the postoperative complications, table (6) showed that there was a significant difference between the groups regarding sore throat at 1 hour, 2 hours and 4 hours postoperatively.…”
Section: <0001mentioning
confidence: 95%
See 1 more Smart Citation